PGV based no-code mid-rise reinforced concrete frame-type building fragilities in İstanbul - Duran, Halil İbrahim. (Thesis (M.S.)-Bogazici University. Kandilli Observatory and Earthquake Research Institute, 2020., 2020)
16 building models representing a building stock in the Zeytinburnu District in İstanbul that includes approximately 800 mid-rise reinforced concrete (RC) frame buildings are used to develop PGV based fragility models that could partially represent the no-code building vulnerability in Turkey. The 3-D analytical models of the subject frames are modeled with distributed plasticity using the Open System for Earthquake Engineering Simulation (OpenSees) software. The damage states of the fragilities are determined by use of the performance limits of structural members from 2018 version of the Turkish Building Earthquake Code and 2005 version of the Eurocode 8. Peak ground velocity (PGV) is preferred as seismic intensity measure since it has a better correlation with deformation demands. 25 real ground motion pairs are selected using disaggregation results of three different PGV hazard curves determined from three ground motion predictive models that are used in the development of the most recent national seismic hazard maps. Response statistics are kept through incremental dynamic analysis (IDA) to develop fragilities for each model. The fragilities computed from above comprehensive nonlinear response history analyses advocate that consideration of variabilities in (a) structural models, (b) ground motion records and (c) limit states makes a huge impact in the exceedance probabilities of damage states. Therefore, a backbone fragility model, which covers the above uncertainties by up and down scaling of a central model is a must in proper loss assessment of building stocks.
Keywords: Reinforced concrete construction -- Standards -- İstanbul.; Earthquake risk analysis.